Analysis of Students' Creative Thinking Abilities through Project-Based Learning in Natural and Social Sciences in Grade Four Elementary School Students - Rizcha Fauziah; Harlinda Syofyan (Journal of English Language and Education, 2026)
Children who think creatively have four indicators, namely originality or the ability to produce new and unique ideas, fluency or the ability to produce many ideas quickly, elaborative or the ability to explain ideas in detail, and flexibility or the ability to think from various perspectives. With project-based learning (PjBL), children can practice their creative thinking skills through learning activities that are tailored to the material taught. This study aims to evaluate students' creative thinking skills through the application of PjBL, especially in science subjects in grade IV B students at SDN Tanjung Duren Selatan 01 Pagi. This study uses a descriptive qualitative method by collecting data through observation, interview, and documentation techniques. The results of the study show that the ability to think creatively through the application of project-based learning in Social Natural Sciences material is not good enough, it can be seen that the fluency indicator has a score of 77.4% and can be categorized as good, then in the flexibility indicator has a score of 19.3%, including the category of less, in the original indicator has a score of 61.2%, it can be categorized as sufficient because there are 3 groups that are able to answer teachers' questions about consumption examples with different answers. Then in the detailing category, having a score of 58.1% can be categorized as sufficient. From these results, it can be seen that there are 4 indicators of creative thinking but only 1 indicator is good, namely smoothness, then 2 other indicators are quite original and detailed, and there is 1 indicator that is still lacking, namely flexibility.